PENGEMBANGAN BUKU CERITA BERGAMBAR BERBASIS BUDAYA LOKAL PADA GURU TK DI LAMONGAN - Made Ayu Anggreni; Andri Kurniawan; Intan Maharani Yusirianti; Rizqi Rahmawati; Maria Antikarma Sugo (LPPM Universitas Bina Bangsa, 2023)
Freedom to learn for early childhood is freedom to play. An educator or teacher must be able to create learning resources that attract the attention of early childhood so that lessons become interesting. One of the learning resources that attracts children's attention is picture story books, which have interesting, colorful pictures and teachers can develop according to themes related to local culture. To maintain culture in an era of rapid globalization, teaching skills developed by creating picture story books introducing local culture to the environment children live in can help prepare early childhood for the future. Through community service activities, the Early Childhood Education Teacher Education Study Program (PG-PAUD) provides training on the development of picture storybooks based on local culture to kindergarten teachers in Lamongan for teaching materials in planning learning with interesting and fun picture book media. This movement is a real effort to improve early childhood literacy learning, aligned with shared reading goals, which include improving education, improving culture, and literacy discourse. Of course, this requires active participation from all parties, including parents, early childhood, teachers, and the community. As part of the implementation of the Pancasila Student Profile Strengthening Project (P5)